(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study examines the impacts of predatory journals on academic institutions based on an exploratory search in Scopus and Web of Science (2014–2024). The analysis shows a rise in publications, highlighting threats to scientific integrity and weaknesses in academic evaluation. The discussion identified three thematic axes: fraudulent publishing practices, institutional impacts, and information ethics. The study concludes that tackling the issue requires institutional guidelines, integrity policies, and critical training in open science.